Studi Komparatif Daya Dukung Pondasi Tiang Pancang Berdasarkan Hasil Pile Driving Analyzer Test dan N-SPT - Muhammad Zulfiqar; Mahfuz Hudori (Jurnal Talenta Sipil, 2023)
The construction of the skidway in the southern part was planned using a pile foundation on the lower structure. Piles are used to channel the load received by the above part of the structure into the ground. The foundation of the structure must have a mast carrying capacity greater than the plan load that the foundation is capable of accepting. This research is important to find out whether the different methods implemented in the field produce different soil carrying capacity. This research will discuss the comparison of pile carrying capacity with field data and testing the carrying capacity of pole foundations. The method of accurate carrying capacity measurement is carried out by static loading with a test method with a loading scale of 2-3 times the planned load. Another method that can be done is HSDPT, which is a high strain dynamics pile test or a pile driving analyzer (PDA) Test. The test results of the analysis showed that there was only a 1% difference in results through an empirical approach with testing with CAPWAP and PDA tests on the southern cpp deck expansion project. The conclusion of this research that the difference in the method used does not have a large enough deviation to the results obtained when construction is carried out in the field.